2023
DOI: 10.1159/000531643
|View full text |Cite
|
Sign up to set email alerts
|

The Ghent Psychotherapy Study: A Pragmatic, Stratified, Randomized Parallel Trial into the Differential Efficacy of Psychodynamic and Cognitive-Behavioral Interventions in Dependent and Self-Critical Depressive Patients

Abstract: <b><i>Introduction:</i></b> Different types of psychotherapy are effective for treating major depressive disorder across groups yet show large within-group differences. Patient personality style is considered a potentially useful variable for treatment matching. <b><i>Objective:</i></b> This study is the first experimental test of the interaction between therapeutic approach and patients’ dependent versus self-critical personality styles. <b><i>Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Studies with intensive longitudinal methods have participants complete multiple self-reports per day for several weeks (e.g., McNeish et al, 2021), and those methods have demonstrated feasibility in several contexts. Clinical trialists also now routinely collect interim observations of self-reported outcomes (e.g., Meganck et al, 2023), which is recommended to better characterize symptoms (Rush et al, 2022). The optimal frequency and number of assessments per person depend on the case at hand, but collecting more than two observations is both desirable and feasible in numerous settings.…”
Section: C the Rci Does Not Account For More Than Two Observations Pe...mentioning
confidence: 99%
“…Studies with intensive longitudinal methods have participants complete multiple self-reports per day for several weeks (e.g., McNeish et al, 2021), and those methods have demonstrated feasibility in several contexts. Clinical trialists also now routinely collect interim observations of self-reported outcomes (e.g., Meganck et al, 2023), which is recommended to better characterize symptoms (Rush et al, 2022). The optimal frequency and number of assessments per person depend on the case at hand, but collecting more than two observations is both desirable and feasible in numerous settings.…”
Section: C the Rci Does Not Account For More Than Two Observations Pe...mentioning
confidence: 99%
“…To illustrate this, we surveyed all 2022 and 2023 issues of Psychotherapy and Psychosomatics which ranks among the highest-impact psychology journals (Impact Factor 2023: 26.617). We found that of 17 studies that reported results of regression analyses [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], only six made use of at least one of these visualizations [22][23][24][25][26][27]. One of them applied a forest plot variant [22].…”
Section: Reporting and Visualizing Regression Modelsmentioning
confidence: 99%